ANALYSIS OF PEDAGOGICAL TEXT AS A STRATEGY OF SCIENTIFIC RESEARCH - Andrey V. Korjuev; Vladimir S. Babaskin; Albina R. Sadykova (Высшее образование в России)
The article focuses on the peculiarities of pedagogical text analysis as a research procedure that should be accomplished by a researcher0beginner. Special attention is paid to a content-analysis of a pedagogical text, which includes conceptual orientation, application area, terminology and logic correctness of an author’s theses and conclusions.